Efisiensi Teknis, Harga, dan Ekonomis pada Usahatani Jagung ( Zea Mays L. ) di Subak Gunung Sari Kawan, Desa Saba, Kecamatan Blahbatuh, Kabupaten Gianyar - DEWA NGAKAN MADE ANGGA DIPARTHA; MADE ANTARA; I MADE NARKA TENAYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Technical Efficiency, Price, and Economical in Farm Corn (Zea MaysL.) at Subak Gunung Sari Kawan, Saba Village, Blahbatuh, GianyarSubak Gunung Sari Kawan is one Subak plant corn. Commodity corn crop isaffected by the factors of production, such as labor, seeds, Urea, NPK, andpesticides, in which the quantity of production factors greatly affect cornproduction. This study aimed to analyze the influence of factors of productionlabor, seeds, Urea, NPK, and pesticides, and analyze the technical efficiency, price ,and economical in corn farming. This study uses multiple linear regression methodthat includes: classic assumption test consisting of normality test, heteroskedasitas,test multikoliniearitas and test the linear regression model that includes: test thecoefficient of determination (R2), F-test and t-test with significance level (?) of 5%.After that tested the model validation by comparing the root mean square error andmean absolute error to determine a more precise forecasting methods used. Theequation used is the production function model of Cobb-Douglas productionfunction of the natural logarithm. The analysis of the equation efficiency include:technical efficiency, price, and economical. Taken together all the factors ofproduction of corn in corn farm real impact on corn production. Partially factors ofproduction the number of seeds (X2) significantly affect corn production, whileother production factors did not significantly affect corn production. Based on theanalysis of technical efficiency, seed production factors (X2), Urea (X3), NPK(X4), and pesticides (X5) technically efficient. Judging from the price efficiencyand economical efficiency of all factors of production there is no efficient.